Probable models of estimation of complex system reliability by means of homogenous Markov chains - Корнійчук, М. Т.; Совтус, І. K.; Семенченко, A. І.; Шутко, M. O.; Сольонов, В. І. (Proceedings of National Aviation University (archive), 1998)
Considered is formalization of formulation and solution of the problem of estimation of reliability of complex radioelectronic systems by means of mass servicing with input non-uniform unified Erlang flow and by the system of exponential servicing which is adopted by devision parameters to the condition of the flow. Formed are the functions which can be interpreted by sufficiently informative way as reliability characteristics of the process of functioning of complex radioelectronic systems